Pemahaman Al-Jibt (Sihir) dalam Perspektif Hadis - Fatrisia, Anggi; Halim, Abdul (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
In the current digital era, the Muslim community faces increasing challenges related to the resurgence of practices reminiscent of the pre-Islamic era, such as witchcraft and paranormal activities, often publicized through social media and television. This phenomenon raises concerns about its impact on the faith of the community. This research aims to delve into and actualize the understanding of jibt and thagut from a hadith perspective, focusing on the application of relevant hadiths in the context of modern life. A qualitative methodology with a thematic analysis approach was employed, utilizing techniques of takhrij al-hadith and syarah al-hadith to evaluate and interpret the hadith texts. The findings indicate that the majority of hadiths discussing al-jibt possess weak chains of narration (sanad), however, the diversity of the narration chains mitigates the severity of these weaknesses. Al-jibt is identified as an illicit and misleading practice, often associated with demonic assistance. These findings are crucial for strengthening the Muslim community’s understanding to avoid being influenced by such misguided practices. This study fills a gap in the literature by providing a detailed analysis of the relevance of hadiths in addressing contemporary issues related to the revival of pre-Islamic practices. Abstrak: Di era digital saat ini, umat Islam menghadapi tantangan yang meningkat terkait kemunculan kembali praktik-praktik yang menyerupai adat jahiliyah, seperti perdukunan dan paranormalisme, yang sering dipublikasikan melalui media sosial dan televisi. Fenomena ini menimbulkan kekhawatiran mengenai pengaruhnya terhadap aqidah umat. Penelitian ini bertujuan untuk mendalami dan mengaktualisasikan pemahaman tentang jibt dan thagut dalam perspektif hadis, dengan fokus pada aplikasi hadis-hadis terkait dalam konteks kehidupan modern. Metodologi yang digunakan adalah kualitatif dengan pendekatan analisis tematik, menggunakan teknik takhrij al-hadith dan syarah al-hadith untuk mengevaluasi dan memahami teks-teks hadis. Hasil penelitian menunjukkan bahwa mayoritas hadis yang mendiskusikan al-jibt memiliki sanad yang dhaif, namun variabilitas jalur sanad mengurangi keparahan kelemahan ini. Al-jibt ditemukan sebagai praktik yang haram dan menyesatkan, seringkali dilibatkan dengan bantuan setan. Temuan ini penting untuk memperkuat pemahaman umat Islam agar tidak terpengaruh oleh praktik-praktik sesat. Penelitian ini mengisi celah dalam literatur dengan menyediakan analisis mendalam tentang relevansi hadis dalam menanggapi isu-isu kontemporer yang berkaitan dengan praktik jahiliyah yang dihidupkan kembali.